Does Artificial Intelligence (AI) Play Roles in Enhancing Academic Writing? Unravelling Lecturers’ Voices in Indonesian Higher Education - Wahyuningsih, Sri (Jurnal Pendidikan Progresif, 2024)
Abstract: Does Artificial Intelligence (AI) Play Roles in Enhancing Academic Writing? Unravelling Lecturers’ Voices in Indonesian Higher Education. Objectives: The rapid advancement of technology has brought about effectiveness and flexibility in the field of education in the digital era. However, in the context of academic writing, the study of AI tools utilization from the perspectives of lecturers across diverse majors has not been explored yet. The present study explores the voices of lecturers on the roles of artificial intelligence (AI) in fostering academic writing. Methods: Anchoring in a qualitative design with a case study approach, data were gathered from semi-structured interviews with six lecturers at an Indonesian higher education. Findings: The findings revealed that some lecturers had positive responses toward the development of artificial intelligence particularly in fostering academic writing. In addition, artificial intelligence (AI) enhances academic writing by promoting efficiency and accuracy, developing consistency, detecting plagiarism in academic writing, and providing information and data to enhance academic writing. However, some challenges in using artificial intelligence for academic writing include the lack of transparency, critical thinking skills, and ethical considerations in using artificial intelligence tools. Conclusion: The study provides implications that the need for academicians especially lecturers to get up to date with technological advancements such as AI tools utilization in academic writing and use them wisely, the need to increase academic writing quality by enriching academic literacy and joining workshops and mentoring programs. Keywords: academic writing; artificial intelligence; digital era; Indonesian higher education; lecturers’ voices.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202436